Effect of pterospartum tridentatum enriched phenolic extract in mitochondrial bioenergetic functions - Ferreira, Fernanda M. (2013)
Pterospartum tridentatum Willk. is an autochthonous and common plant in Portugal, locally known as ‘carqueija’. Leaves and stems are normally used in cooking, to flavour rice, roast meat or hunting animals and leaves are also used as condiment in fresh salads. Despite its traditional use, no evaluation in mitochondrial bioenergetics has been performed. P. tridentatum leaf extract phenolic composition was elucidated by electrospray ionization-mass spectrometry (ESI-MS). M. aquatica extract effects were evaluated over mitochondrial membrane potential by using a Clarktype oxygen electrode in the presence of succinate as respiratory substrate. Cytotoxicological effects of plant extracts were evaluated on HepG2 cells throughout MTT assay. The ESI-MS spectrum of P. tridentatum leaves aqueous extract revealed the presence of several luteolin and isorhamnetin derived phenolic compounds, which can be associated to the health benefits claimed for this plant species. Yet, P. tridentatum leaves extract (up to 100 lg plant extract mg protein _1) stimulated state 4 and FCCP-stimulated liver mitochondria respiratory rates and inhibited the state 3 respiratory rate. Hence, respiratory control ratios were diminished, indicating a phosphorylative efficiency decrease, due to inner mitochondrial membrane permeability induced by P. tridentatum leaves extract. Nevertheless, P/O ratios were not affected in the range of concentrations tested and cytotoxicity evaluation using MTT assay (50 and 125 ug plant extract) showed no significant decrease over HepG2 cell viability. This dual behaviour reflects the P. tridentatum hormetic effects over mitochondrial activity. Conclusion: Overall, the present study suggests that consumption of P. tridentatum leaves should be regarded as safe and present benefits concerning the modern lifestyles.